Heating time required for an MgO-graphite refractory during a hot modulus of rupture test - Baldo, J. B.; Dos Santos, W. N.; Paskocimas, C. A.; Cava, S.; Pianaro, S. A.; Longo, Elson [UNESP] (My University, 2006)
In the work described in the present paper, an analytical solution of the general heat conduction equation was employed to assay the temperature profile inside a solid slab which is initially at room temperature and is suddenly plunged into a fluid maintained at a high temperature. The results were then extrapolated to a simulation of a hot modulus of rupture test of typical MgO-graphite refractory samples containing different amounts of graphite in order to evaluate how fast the temperature equilibrates inside the test specimens. Calculations indicated that, depending on the graphite content, the time to full temperature homogenization was in the range of 80 to 200 s. These findings are relevant to the high temperature testing of such refractories in oxidizing conditions in view of the graphite oxidation risks in the proper evaluation of the hot mechanical properties.
Keywords: Hot modulus of rupture test; MgO-graphite refractories; Oxidation layer; Oxidation layers; Graphite; Heat conduction; Mechanical properties; Oxidation; Refractory materials; Thermodynamic properties; Magnesia